The impact of digital transformations on business leadership: A bibliometric approach - Moreira, Isaac (2022)
Digital transformation (DT) has aroused interest in recent dec- ades in the academic world. Several studies have been published in this sense, as it becomes a challenge for management teams to lead in an environment of constant technological evolution. Indeed, this study has a twofold objective: to map the thematic evolution of research on the impact of DT on business leader- ship and elaborate a conceptual framework that brings together the ideas and concepts of other researchers. Based on the main objective, 44 articles published between 2012 and 2022 were collected from the Web of Science. Taking into account the collected sample, 17 articles correspond to exploratory stud- ies, 15 articles to qualitative studies, 7 to quantitative studies and 5 to mixed methodology studies. Considering the results obtained, the studies under analysis are divided into 4 clusters, according to their contribution to the theme under analysis: i) Digital Transformation; ii) Industry 4.0; iii) Strategic People Management and iv) Innovation. The first cluster comprises 17 articles, the second contains 14 articles, the third comprises 7 articles and the fourth and last cluster results in 6 articles. Con- sidering that the topic under investigation has been the subject of emerging research, the developed framework is understood as a solid basis for continued discussion and future research.